2020
DOI: 10.17221/20/2019-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic fidelity of in vitro-propagated blackberry plants using RAPD and SRAP molecular markers

Abstract: The aim of this research was to evaluate the genetic uniformity of blackberry plants (Rubus fruticosus L. ‘Loch Ness’ and ‘Chester Thornless’) obtained by micropropagation. Genetic uniformity was analysed by using RAPD and SRAP markers. For the in vitro multiplication, the slightly modified Murashige and Skoog (1962) basal medium was used, supplemented with 0.5 mg/l 6-Benzyladenine (BA), prepared with tap water and 50 g/l wheat starch as the gelling agent. This culture medium ensured the regeneration of well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…In order to assess the genetic variability of berry plants, the RAPD and ISSR markers are most frequently used. In several research papers, the use of AFLP, SSR, and SRAP markers was also reported [17,19,21,25,[61][62][63]65,[70][71][72]. AFLP analysis proved to be more reliable and sensitive than other methods not only in our research, but also in the studies of Lanham and Brennan [21] and Costa and co-workers [31].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In order to assess the genetic variability of berry plants, the RAPD and ISSR markers are most frequently used. In several research papers, the use of AFLP, SSR, and SRAP markers was also reported [17,19,21,25,[61][62][63]65,[70][71][72]. AFLP analysis proved to be more reliable and sensitive than other methods not only in our research, but also in the studies of Lanham and Brennan [21] and Costa and co-workers [31].…”
Section: Discussionsupporting
confidence: 72%
“…In plants derived from four-year pineapple in vitro cultures, the analysis, with the use of RAPD markers, showed as much as 95.9% variability [64]. On the other hand, Borsai and co-workers [65], using sequence-related amplified polymorphism (SRAP) and RAPD markers, did not detect any polymorphism in plants of blackberry cv. Loch Ness and Chester Thornless propagated for both 3 and 11 subcultures.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes are often temporary, and plants may revert to the normal phenotype relatively easily (Jain 2001;Smulders & de Klerk 2011). Molecular markers become the most desirable tool for establishing genetic uniformity of in vitro derived plantlets of different plant species, including berry plants such as lowbush blueberry, strawberry and blackberry (Debnath 2011(Debnath , 2013Borsai et al 2020). To date, there is no genetic stability assessment system for micropropagated plants of blue honeysuckle.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…The genome profiling of plants with pharmaceutical value, using different molecular fingerprinting methods, was reviewed by Gantait et al [ 6 ]. Several of these methods have been applied to address the genetic fidelity of in vitro propagated plants, examples include Hedychium coronarium by inter simple sequence repeats (ISSR) [ 7 ], the endangered medicinal plant Rauwolfia tetraphylla , by start codon targeted polymorphism (SCoT), ISSR, and random amplified polymorphic DNA (RAPD) [ 8 ], Helianthus verticillatus in vitro raised plants using SSRs [ 9 ] and the blackberry ( Rubus fruticosus L.) using RAPD and sequence-related amplified polymorphism (SRAP) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%